Management Report in accounting and management of innovation activities - Radelytskyy, Yuriy; Holubetskyy, Pavlo; Lizanets, Mariana (Herald of Economics, 2026)
The spread of integrative approaches in accounting and control practices has contributed to the development of a new form of disclosure – external management reporting. This report unites the characteristics of traditional financial statements and internal managerial reports by presenting both financial and non-financial metrics within a single informational framework aimed at satisfying the needs of a wide range of stakeholders. Existing external reporting formats do not adequately reflect innovation-related processes, which highlights the need to explore improved methods for presenting comprehensive indicators of a company’s innovative activity tailored to the information demands of various user groups. Purpose of the article is to clarify the interrelationship between the Management Report and other forms of reporting and to develop a recommended structure and content of the report that take into account the specifics of a company’s innovation activity. The necessity of expanded disclosure of information on a company’s innovation activity in external management reporting is substantiated in view of its limited presentation in regulated financial statements. It is proposed that indicators of innovation activity in the Management Report be structured according to the following sections: the role of innovation activity among the company’s functional areas, innovation units within the organizational structure; the impact of innovation generation and adoption processes on performance; the impact of innovation activity on financial indicators; environmental innovations and their environmental impact; innovations in ensuring social standards and HR policy; risks related to the generation and implementation of innovations; the list of innovation projects with presentation of their variable parameters; the interrelationship between innovation and investment activities; innovation-driven development trends; and the orientation of innovation activity toward internal stakeholders. The expediency of addressing the information needs of not only internal but also external stakeholders in the Management Report is substantiated. It is demonstrated that preparing external management reporting in an electronic format with the use of graphical elements, analytical tables, interactive forms, and expert commentary enhances the comprehensibility of reporting indicators and enables controlled disclosure of confidential information in compliance with the requirements for protecting trade secrets related to a company’s innovation processes. Expanded disclosure of information on innovation activity in the Management Report increases the informational value of external management reporting and ensures a comprehensive reflection of the impact of innovation on various aspects of a company’s operations. The use of an electronic reporting format with analytical and visual elements improves stakeholders’ understanding of the data while ensuring compliance with confidentiality requirements.